Web-Based Student Payment Administration Information System Using The Waterfall Method - Mahmud Mustapa; Erwin Gatot Amiruddin; Ezra Maharani Chaniago; Ummiati Rahmah (Ceddi Journal of Education, 2023)
This research aims to develop an Information System that can assist the school admin in providing the validation process for tuition payments, speed of access, and completeness in providing information. This research aims to overcome administrative challenges that often occur in schools, such as errors in recording payments, late payments, and the difficulty of tracking payment history to save time and effort previously spent processing payments manually. The research method used is the Waterfall method. This application will make it easier for the finance department to record student tuition payments method was chosen because of its deep capabilities and describes a flow or stages that run like a waterfall from one stage to the next. This approach relies heavily on good initial planning because changes made in the early stages may be difficult or expensive to implement in later stages. Based on the results of system design and black box testing, it can run well, and user responses also provide very good responses, with 94% of respondents giving very good responses and 0% saying good and quite good. Based on these findings is hoped that it can be used more efficiently and also ensure data security and can store the results of the data that has been processed.